Pengaruh Pengetahuan Kewirausahaan, Motivasi dan Kreativitas Terhadap Minat Berwirausaha Pada Mahasiswa Universitas HKBP Nommensen Medan - Gulo, Nifarius; Siagian, Nalom; Sinaga, Kepler (Jurnal GeoEkonomi, 2026)
This learn uses a quantitative research method with data obtained through a survey of individuals who meet the criteria, using Structural Equation Modeling method as a way to analyze the influence of entrepreneurial knowledge, motivation and creativity on entrepreneurial interest in students of HKBP Nommensen University Medan. Grounded in the effect and discussions in this learn regarding the leverage of pioneering insight, ambitious Motivation and Entrepreneurial Creativity on Entrepreneurial attention inside scholar of HKBP Nommensen Collage Medan, and can be proven by 180 respondents with 18 statements, the following conclusions can be drawn: (1) Entrepreneurial Knowledge This can seen from this Probability of 0.001, where the quantity is reduced than this critical 0,05. can be concluded that entrepreneurial knowledge is able to influencer entrepreneurship interest. (2) Entrepreneurial of Motivation has very significantion influence entrepreneurial interesting. This can be seen from the Probability 0.002, where the value is lesser than this critical 0,05. It can concluded entrepreneurial motivation able to influence entrepreneurial interest. (3) Entrepreneurial Creativity has very significant influencer on entrepreneurialship interest. This can be from the Probability value of 0.002, where the value is smaller than the critical 0.05. It can be concluded that entrepreneurial motivation is able to influence entrepreneurial interest